Identification of Ex Ante Returns Using Elicited Choice Probabilities: An Application to Preferences for Public-Sector Jobs - Romuald Meango; Esther Mirjam Girsberger (Institute of Labor Economics (IZA), 2024)
Ex ante returns, the net value that agents perceive before they take an investment decision, are understood as the main drivers of individual decisions. Hence, their distribution in a population is an important tool for counterfactual analysis and policy evaluation. This paper studies the identification of the population distribution of ex ante returns using stated choice experiments, in the context of binary investment decisions. The environment is characterised by uncertainty about future outcomes, with some uncertainty being resolved over time. In this context, each individual holds a probability distribution over different levels of returns. The paper provides novel, nonparametric identification results for the population distribution of returns, accounting for uncertainty. It complements these with a nonparametric/semiparametric estimation methodology, which is new to the stated-preference literature. Finally, it uses these results to study the preference of high ability students in Côte d'Ivoire for public-sector jobs and how the competition for talent affects the expansion of the private sector.
Keywords: C21; C23; D84; J21; J24; J30; J45; 330; subjective expectations; ex ante returns; nonseparable panel; distribution regression; job search; public sector